2018
DOI: 10.1111/eip.12741
|View full text |Cite
|
Sign up to set email alerts
|

Latent profile analysis of psychosis liability in a community‐derived sample of adolescents: Links with mental health difficulties, suicidal ideation, bipolar‐like experiences and psychotic‐like experiences

Abstract: Aim The main goal of the present study was to explore the latent structure of schizotypy as an indicator of psychosis liability, in a community‐derived sample of adolescents. Links to mental health difficulties, prosocial behaviour, suicidal ideation, bipolar‐like experiences and psychotic‐like experiences (PLEs) (severity and distress) were compared across schizotypy latent profiles. Method The present research included 1588 adolescents selected by a stratified random cluster sampling. The Oviedo Schizotypy A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 62 publications
5
12
0
Order By: Relevance
“…They found that schizotypal features were highly overlapped with depressive symptoms. Furthermore, the results found here are congruent with those studies that show that PLEs during adolescence are associated, among other, with emotional and behavioural problems, suicidality, and depression (Armando et al, 2010;Bolhuis et al, 2018;Fonseca-Pedrero et al, 2019;Kelleher et al, 2013;Schimanski, Mouat, Billinghurst, & Linscott, 2017;Yung et al, 2006). Overall, the results add empirical support to the extended psychosis phenotype indicating that PLEs (occurrence and associated distress) are directly associated with emotional dysregulation and psychopathology in adolescent populations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They found that schizotypal features were highly overlapped with depressive symptoms. Furthermore, the results found here are congruent with those studies that show that PLEs during adolescence are associated, among other, with emotional and behavioural problems, suicidality, and depression (Armando et al, 2010;Bolhuis et al, 2018;Fonseca-Pedrero et al, 2019;Kelleher et al, 2013;Schimanski, Mouat, Billinghurst, & Linscott, 2017;Yung et al, 2006). Overall, the results add empirical support to the extended psychosis phenotype indicating that PLEs (occurrence and associated distress) are directly associated with emotional dysregulation and psychopathology in adolescent populations.…”
Section: Discussionsupporting
confidence: 89%
“…At a phenotypic level, the link between psychotic experiences and a later psychotic disorder, may be stronger depending on the concomitant presence of affective dysregulation, family history of a mental disorder, and lower socio-economic status (Klrll et al, 2019;Pries et al, 2018;van os & Linscott, 2012). In addition, previous research has shown that PLEs are also associated bidirectionally, among others, with emotional and behavioural problems, suicidality, non-suicidal self-injury, depression, and substance use (Armando et al, 2010;Bolhuis et al, 2018;Fonseca-Pedrero, Ortuño-Sierra, Muñiz, & Bobes, 2019;Yung et al, 2006). In this sense, evidence suggests that the combination of well-known risk factors such as cannabis use, psychopathology, childhood adversity, and urbanicity, in interaction with proxy measures of genetic risk, may facilitate the onset of psychosis (eg, Radhakrishnan et al, 2019).…”
mentioning
confidence: 99%
“…The adolescents in the true schizotypy latent class reported more psychological distress and family history of psychosis, compared to the other classes. In other study, Fonseca-Pedrero et al [31], using a representative sample of adolescents, found four latent profiles (positive schizotypy, low schizotypy, social disorganization schizotypy, and high schizotypy), where the high schizotypy class scored higher on psychopathology indicators relative to the other three clusters.…”
Section: Introductionmentioning
confidence: 87%
“…There is an increasing interest in finding homogenous groups of potentially at-risk individuals based on psychotic-spectrum phenomena [31,32]. A novel mixture model called latent class analysis (LCA) (dichotomous outcome) or latent profile analysis (LPA) (continuous outcome) [33] was recently used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Meng et al conducted an LPA on a sample of 2158 participants and found a best-fitting model with three classes: ‘low group anxiety, moderate group anxiety and high group anxiety’ 9. Fonseca-Pedrero et al using LPA identified four latent classes: ‘positive schizotypy’, ‘low schizotypy’ and ‘high schizotypy’ and their findings can facilitate prevention of psychotic-spectrum disorder and mental health problems 17…”
Section: Introductionmentioning
confidence: 99%